Determinação de resíduos de agrotóxicos em manga empregando método QuEChERS e UHPLC-MS/MS - Machado, Franciele Fátima (2022)
Pesticides are applied from the development of the plant to its production, transport and storage. When not applied correctly, these chemicals can cause harm to human health and the environment. Thus, this work aimed to develop and validate an analytical method for the determination multiresidue of pesticides in mango, using the original QuEChERS method and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/MS). The dispersive solid phase extraction (d-SPE) technique was used to clean the extracts with Strata™-X as sorbent. The method was validated for 60 compounds and the results indicated that the applied method is linear in the range of 0.5 to 20 μg L-1. Precision and accuracy were evaluated at four spike levels, namely: 5, 10, 25 and 50 μg kg-1 (n= 5), showing recoveries between 70 and 120%, with RSD ≤ 20%. The method limits of quantification ranged from 5 to 10 μg kg-1 for most of the pesticides and the limits of detection from 1.5 to 3 μg kg-1. To evaluate the validation and intermediate precision of this method, it was applied to sixteen commercial samples of mango. The applicability of the method was performed by analyzing sixteen commercial samples and the results showed the presence of pesticide residues with concentrations below what is allowed by Brazilian legislation and pesticides prohibited for mango cultivation, such as carbendazim.